Ethernet's high-wire act [new IEEE standard]. - Cherry, S.
The local- and metropolitan-area networking committee of the IEEE 802.1 working group has been tasked to develop a standard that could ensure the high quality of service needed to transmit streaming multimedia over a wide-area Ethernet network that covers an entire city. The new standard hopes to make possible dramatic improvements in services such as Internet-based television. Once the standard is in place, costs are expected to drop for carriers, which can pass those savings on to the users of their high-speed services.
Keywords: Ethernet; IEEE 802.1 working group; IEEE 802.1ah.; Web page; Websights; Broadband data; Data networks; Local-area networking; Streaming multimedia; Voice over IP; Wide-area Ethernet network